Sol-Gel Synthesis of Chelate Containing Materials for Gas Chromatography; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Gavrilenko M. A. Mikhail Alekseevich; Slizhov Y. G.; Faustova Z. V.; Kasymova T. A. Tatiana Aleksandrovna; Gavrilenko N. A. Natalia Airatovna (Chemical Technologies, 2014)
Title screen